MODEL KEPEMIMPINAN KEPALA SEKOLAH PENGGERAK MENUJU PENDIDIKAN BERMUTU INTERNASIONAL - SARI, HERLINA; NOR, TAUFIK; SURIANSYAH, AHMAD; SULISTYANA, SULISTYANA (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
This research discusses the Sekolah Penggerak Program, School Transformation and the Scope of the Sekolah Penggerak Program. The Sekolah Penggerak Program is an effort to realize the vision of Indonesian Education in realizing an advanced Indonesia that is sovereign, independent and has personality through the creation of Pancasila Students. The Sekolah Penggerak Program focuses on developing holistic student learning outcomes which include competency (literacy and numeracy) and character, starting with superior human resources (school principals and teachers). The Sekolah Penggerak Program is a refinement of the previous school transformation program. The Sekolah Penggerak Program will accelerate public/private schools in all school conditions to move 1-2 stages further forward. This research was carried out through a literature study by collecting a number of literature in the form of books and journals related to driving teachers and analysis of the data used was critical to explore more deeply about driving teachers and the role of driving teachers. ABSTRAKPenelitian ini membahas tentang Program Sekolah Penggerak, transformasi Sekolah dan Ruang Lingkup Program Sekolah Penggerak. Program Sekolah Penggerak adalah upaya untuk mewujudkan visi Pendidikan Indonesia dalam mewujudkan Indonesia maju yang berdaulat, mandiri, dan berkepribadian melalui terciptanya Pelajar Pancasila. Program Sekolah Penggerak berfokus pada pengembangan hasil belajar siswa secara holistik yang mencakup kompetensi (literasi dan numerasi) dan karakter, diawali dengan SDM yang unggul (kepala sekolah dan guru). Program Sekolah Penggerak merupakan penyempurnaan program transformasi sekolah sebelumnya. Program Sekolah Penggerak akan mengakselerasi sekolah negeri/swasta di seluruh kondisi sekolah untuk bergerak 1-2 tahap lebih maju. Penelitian ini dilaksanakan melalui studi pustaka dengan mengumpulkan sejumlah literature berupa buku, dan jurnal yang berkaitan dengan guru penggerak dan Analisis data yang digunakan adalah kritis untuk menelusuri lebih mendalam tentang guru penggerak dan peran guru penggerak.